Microinfiltração em restaurações com resinas compostas de baixa contração de polimerização - Junior, Geraldo Marcio de Azevedo (2020)
The aim of this in vitro study was to assess the marginal microleakage in restorations with different bulk-fill resin composite (RBC) when compared with a conventional resinbased composite (RC). Standardized cavities in the buccal aspect of bovine central